Low birth weight was the most dominant predictor associated with stunting among children aged 12–23 months in Indonesia. Issue 1 (December 2017) - Aryastami, Ni; Shankar, Anuraj; Kusumawardani, Nunik; Besral, Besral; Jahari, Abas; Achadi, Endang
Abstract Background Stunting among toddlers is highly prevalent in Indonesia. As a chronic malnutrition problem, stunting is closely related to internal (maternal health) and external factors such as feeding practices, illness and socio-economics of the community. The purpose of this study was to analyze the relationship between low birth weight (LBW), child feeding practices and neonatal illness with stunting among Indonesian toddlers. Methods For this study, we took data from the 2010 Indonesian National Basic Health Survey (RISKESDAS). Totally 3024 children aged of 12–23 months included in this analysis. Stunting was measured using standardized body length and was defined based on criteria from WHO AnthroII.PC2007. Data analysis was done through bivariate and multivariate logistic regressions. Results The results showed that the prevalence of stunting among Indonesian toddlers (12 23 months) was 40.4%. Early initiation of breast-feeding and exclusive breast feeding was experienced by 42.7% and 19.7% of the babies. More than half of the babies were given pre-lacteal feeds, while early complementary feeding was given to 68.5% of the subjects. Multivariate analysis showed infants born with LBW were 1.74 times more likely to be stunted (95% CI 1.38–2.19) than those born with normal weight. Boys were 1.27 times (95% CI 1.10–1.48) more likely to be stunted than girls. Infants with a history of neonatal illness, they were 1.23 times (95% CI 0.99–1.50) more susceptible to stunting. Being poor was another indirect variable that significantly associated with stunting (OR = 1.3, 95% CI 1.12–1.51). Conclusion LBW, gender (boys), history of neonatal illness and poverty are factors related to stunting among children aged 12–23 months in Indonesia, with LBW being the major determinant of stunting.